2016
DOI: 10.1002/ejoc.201600937
|View full text |Cite
|
Sign up to set email alerts
|

Cyclisations Catalysed by Bismuth(III) Triflate

Abstract: Cyclisation reactions have always drawn the attention of organic chemists in pursuit of methods for the selective construction of natural‐product‐like polycyclic compounds. The search for new and efficient ring‐forming reactions has witnessed growing interest, resulting in the design of many elegant synthetic strategies and the discovery of useful methodologies. In this context, cycloisomerisation reactions are very attractive, because they allow for the rapid generation of molecular complexity with use of a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 111 publications
(100 reference statements)
1
31
0
Order By: Relevance
“…The recycling of catalyst has been an important requirement in decreasing environmental pollution and reducing the cost in the industrial process . There is some debate about the nature of active species such as a low‐concentration of triflic acid, which is formed in the hydrolysis of bismuth triflate . However, Lambert and coworkers reported that Bi(OTf) 3 in the presence of substrates indicate that Lewis acid/base interactions are necessary to liberate TfOH .…”
Section: Resultsmentioning
confidence: 99%
“…The recycling of catalyst has been an important requirement in decreasing environmental pollution and reducing the cost in the industrial process . There is some debate about the nature of active species such as a low‐concentration of triflic acid, which is formed in the hydrolysis of bismuth triflate . However, Lambert and coworkers reported that Bi(OTf) 3 in the presence of substrates indicate that Lewis acid/base interactions are necessary to liberate TfOH .…”
Section: Resultsmentioning
confidence: 99%
“…The reaction at 40°C (entry 9) gave 3a as a major product (47%). When we carried out the reaction at 25°C, 3a was obtained in good yield (55%) …”
Section: Methodsmentioning
confidence: 99%
“…[4] In this area, bismuth(III) triflate is known for its wide applicability to the activation of various chemical functions in cyclisation reactions. [5] Recently, we developed new cyclisation reactions involving functionalised enol ethers displaying a tertiary alcohol motif and an alkene [6] or an allene [7] function. Specifically designed enol ethers were shown to undergo tandem cyclisations under acidic conditions, leading to the formation of oxanorbornane spirocyclic diethers (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our ongoing research on Lewis superacid‐catalysed reactions, our interest was focused on the development of new catalytic methodologies for the preparation of novel fragrance ingredients . In this area, bismuth(III) triflate is known for its wide applicability to the activation of various chemical functions in cyclisation reactions …”
Section: Introductionmentioning
confidence: 99%